2010
DOI: 10.1007/s00216-010-3720-x
|View full text |Cite|
|
Sign up to set email alerts
|

SPE and LC-MS/MS determination of 14 illicit drugs in surface waters from the Natural Park of L’Albufera (València, Spain)

Abstract: A simple and robust method using solid-phase extraction (SPE) and liquid chromatography tandem mass spectrometry (LC-MS/MS) for the simultaneous determination of 14 drugs of abuse and their metabolites (cocainics, amphetamine-like compounds, cannabinoids, and opiates) in surface waters has been developed. Seven SPE adsorbents (Oasis HLB, Oasis MCX, Oasis Wax, Supelselect HLB, Strata-X, Strata-XCW), amount of sorbent bed, water volume, and pH were investigated. The highest recoveries, as well as the simplest pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 35 publications
4
34
0
2
Order By: Relevance
“…In 2005 they identified the presence of cocaine in the Po river at the concentration of 1.2 ng/dm 3 and raw and treated wastewater at the concentration of 120 ng/dm 3 and 42 ng/dm 3 , respectively [85,86]. Other studies confirmed the presence of narcotics in Italy, United States of America, Spain, Ireland and Belgium [87][88][89]. Some compounds like codeine, cocaine or morphine are both medical and intoxicating drugs.…”
Section: Presence Of Narcotics In Surface Ground and Drinking Watermentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005 they identified the presence of cocaine in the Po river at the concentration of 1.2 ng/dm 3 and raw and treated wastewater at the concentration of 120 ng/dm 3 and 42 ng/dm 3 , respectively [85,86]. Other studies confirmed the presence of narcotics in Italy, United States of America, Spain, Ireland and Belgium [87][88][89]. Some compounds like codeine, cocaine or morphine are both medical and intoxicating drugs.…”
Section: Presence Of Narcotics In Surface Ground and Drinking Watermentioning
confidence: 99%
“…methamphetamine and ephedrine, belong to the group of psychostimulants that enhance dopaminergic and noradrenergic transmittance and to a lesser extent serotonergic transmittance. They are used in treatment of attention deficit hyperactivity disorder (ADHD) in children [8,87,89].…”
Section: Presence Of Narcotics In Surface Ground and Drinking Watermentioning
confidence: 99%
“…Oasis HLB) in off-line or on-line mode (Table S1). More details on analytical methodology can be found elsewhere (Castiglioni et al, 2006;Kasprzyk-Hordern et al, 2008;Postigo et al, 2008;Bijlsma et al, 2009;Hogenboom et al, 2009;van Nuijs et al, 2009;Terzic et al, 2010;Vazquez-Roig et al, 2010;Reid et al, 2011a;González-Mariño et al, 2012). The analytical technique of choice for the quantitative analysis of the target drug residues was liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS).…”
Section: Analytical Methodologymentioning
confidence: 99%
“…A influência de tipos de fases extratoras e parâmetros de extração tem sido bastante publicada. 32,34,52,53,75,76 González-Mariño e colaboradores 91 investigaram de forma pioneira o uso de polímero molecularmente impresso (MIP, molecularly imprinted polymer) para extração em fase sólida de AMP e obtiveram resultados satisfatórios.…”
Section: Preparo De Amostrasunclassified